Space-time cube approach in analysing conflicts in Africa - Adams Osman; Alex Barimah Owusu; Kofi Adu-Boahen; Emmanuel Atamey (Social Sciences and Humanities Open, 2023)
In terms of conflict types and occurrences, there is a mesh of old, new, and concurrent conflicts which coexist and are affecting each other over space and time. Existing conflict studies are unable to fully explicate the space-time elements, hence this generates static and two-dimensional hotspots/coldspots. Using Africa as a case, this study used three-dimensional space-time cube, with conflict occurrences grouped into bins where space is mapped horizontally and time is mapped vertically for analysis. Analysis of conflict based on the three dimensional space-time cube produced four main categories of hotspots namely consecutive, sporadic, oscillating, and new hotspots. Furthermore, the causes of conflicts in Africa varied significantly across each time-based hotspot, providing insight into why straightjacket solutions have been unsuccessful. Conflict managers can learn from the patterns of time-based hotspots which helps to see conflicts as three-dimensional entities needing with three levels of orientation that focus on type, space, and time instantaneously.